2021
DOI: 10.1037/cfp0000156
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner aggression during the early parenting years: The role of dissatisfaction with division of labor and childcare.

Abstract: The high rates of intimate partner aggression (IPA) among new parents may be partly due to changes in couples' division of household labor and childcare, which disproportionately negatively impact women. This is the first study to examine the association between division of labor dissatisfaction and IPA perpetration across genders while also examining whether such dissatisfaction is specifically associated with IPA during conflicts about division of labor issues. Quarterly for 1 year, 109 women and 94 men from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As such, it is possible that these conflicts, although relatively minor, can be wearisome for partners potentially due to their more frequent nature. A recent study by Wong et al (2021) also suggested that the division of labor and childcare and work-related stress are topics that often lead partners' conflicts to escalate into verbal and psychological violence. In essence, although they can be considered minor or even insignificant, conflicts about daily annoyances have the potential to be particularly distressing for partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is possible that these conflicts, although relatively minor, can be wearisome for partners potentially due to their more frequent nature. A recent study by Wong et al (2021) also suggested that the division of labor and childcare and work-related stress are topics that often lead partners' conflicts to escalate into verbal and psychological violence. In essence, although they can be considered minor or even insignificant, conflicts about daily annoyances have the potential to be particularly distressing for partners.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 796 community couples, Wheeler and Kerpelman (2016) also found that couples who reported more conflicts surrounding intimacy reported lower relationship satisfaction. Issues surrounding money, trust, sex (Reese‐Weber et al, 2015), or the division of labor and childcare (Wong et al, 2021) have also been found to be associated with higher levels of intimate partner violence, a known correlate of relationship dissatisfaction (Lefebvre et al, 2021).…”
Section: The Topics Of Conflictmentioning
confidence: 99%